No benefit of an adjunctive phototherapy protocol in treatment of periodontitis: A split‐mouth randomized controlled trial. (17th May 2021) - Preshaw, Philip M.; Ide, Mark; Bissett, Susan M.; Holliday, Richard; Lansdowne, Nichola; Pickering, Kimberley; Taylor, Judy A.; Levonian, Ana M.; Pleasance, Christine; Guarnelli, Maria Elena; Simonelli, Anna; Fabbri, Chiara; et al.
Abstract: Aim: To assess the efficacy of a commercially available adjunctive phototherapy protocol ("Perio‐1") in treatment of periodontitis. Materials and Methods: In an examiner‐blind, randomized, controlled, split‐mouth, multicentre study, 60 periodontitis patients received root surface debridement (RSD) in sextants either alone (control sextants) or with the adjunctive phototherapy protocol (test sextants). Re‐evaluation was performed at 6, 12 and 24 weeks. Results: No statistically significant differences in mean (± standard deviation) clinical attachment level (CAL) change from baseline to week 24 were observed between test (−1.00 ± 1.16 mm) and control sextants (−0.87 ± 0.79 mm) at sites with probing pocket depths (PPDs) ≥5 mm ("deep sites") at baseline ( p = .212). Comparisons between test and control sextants for all other parameters (CAL change at all sites, PPD change at deep sites/all sites, bleeding on probing, plaque scores), and for all change intervals, failed to identify any statistically significant differences. Conclusions: The phototherapy protocol did not provide any additional clinical benefits over those achieved by RSD alone. (German Clinical Trials Register DRKS00011229).